The ROLE OF THE LIBRARIAN AS AN ENVIRONMENTAL EDUCATOR AND THEIR CONTRIBUTIONS SUPPORTED BY MEANINGFUL LEARNING - Oliveira, Mariana Paranhos de; Rosa, Sabrina Silveira da; Teixeira, Maria do Rocio Fontoura (Informação em Pauta, 2021)
Libraries, heritage preservation spaces and inseparable from education, are vital for social development and the environmental preservation of the societies in which they are located. Being non-formal learning space, they stand out, because it is through the mediation with the users in the search for information that meaningful learning occurs. Following that line of thought, it is proposed to reflect on libraries as learning spaces, based on a bibliographic review and discusses the contribution of the librarian to Environmental Education as an educator. Therefore, the librarian must collaborate so that the conscious environmental information is assimilated by the users to investigate their ecological practices.